M. Butterfly - Hwang, David Henry 1957- (New York Penguin Group, 1988)
During the Cultural Revolution in China in the mid-1960s, a French diplomat falls in love with a singer in the Beijing Opera, not knowing that the object of his affection is a man. Interwoven with allusions to the Puccini opera "Madama Butterfly", a story of love and betrayal unfolds.--Adapted from imdb.com
Title also given as M. with an illustration of a butterfly.
"Previously published ... in American theatre magazine."
"A Plume book."
Keywords: Love -- Drama; Deception -- Drama; Female impersonators -- Drama; Actors -- China -- Drama; China -- Drama